KUALITAS FOTO POLOS PASIEN DENGAN DAN TANPA LAVEMENT - Panji Wibowo Nurcahyo (JRI (Jurnal Radiografer Indonesia), 2022)
ABSTRACT Introduction: Patient preparation aims to minimize the appearance of air and feces which can interfere with doctors assessing anatomy and pathology on radiographs, and in some cases can even cause a delay in IVP examination. The results showed that there was no statistically significant difference between KUB examination patients with and without patient preparation (Abbasi A, Siyal A and Soomro M.I, 2015). Preparation of IVP patients between outpatients and inpatients at Prof. Hospital. Dr. Margono Soekardjo Purwokerto differs in the presence or absence of lavement. Method: This type of research is descriptive research. The population of the study was request sheets for photos and plain photo radiographs for BNO IVP examination with indications of hydronephrosis. The exclusion criteria for this study were patients aged ≥ 50 years to avoid the effects of constipation. The assessment uses a questionnaire that refers to The European Commission Guideline For Evaluation Of Radiographic Images and the assessment criteria determined by the researcher. Results: up to 6 patients came from the Inpatient Installation and 6 patients came from the Outpatient Installation. Inpatient installation has a higher total score for renal outline. Inpatient installation has a lower total score for visualization of the right psoas line and bone system, but gives the same score for the left psoas line. The Inpatient Installation has a higher total score for visualizing a lot of air and feces than the Outpatient Installation for the proximal colon area, while the distal colon area has the same score. In the distal colonic area, more radiographs from inpatient settings show air and stool features that may interfere with diagnosis than outpatient settings. This can be caused by visits from guests when visiting patients. The tendency of guests to bring food and chat with patients can affect this. Conclusion: In general, radiographs from outpatients and inpatients can clearly show the organs which include, the entire urinary tract area from the upper pole of the kidney to the basal bladder, renal outline, psoas line and bone system, but visualization of a lot of air and feces is more higher than the Outpatient Installation for the proximal colon area, while the distal colon area has the same score.